Nicotinic acetylcholine receptors: Therapeutic targets for novel ligands to treat pain and inflammation - Arik J. Hone; J. Michael McIntosh (Elsevier, 2023)
Nicotinic acetylcholine receptors (nAChRs) have been historically defined as ligand-gated ion channels and function as such in the central and peripheral nervous systems. Recently, however, non-ionic signaling mechanisms via nAChRs have been demonstrated in immune cells. Furthermore, the signaling pathways where nAChRs are expressed can be activated by endogenous ligands other than the canonical agonists acetylcholine and choline. In this review, we discuss the involvement of a subset of nAChRs containing α7, α9, and/or α10 subunits in the modulation of pain and inflammation via the cholinergic anti-inflammatory pathway. Additionally, we review the most recent advances in the development of novel ligands and their potential as therapeutics.